The switching function analysis of power electronic circuits - Marouchos, C. C. (Christos C.) (London, United Kingdom Institution of Engineering and Technology, 2006)
The book is arranged into five parts divided into 21 chapters. The first part deals with switching function. The second part covers AC to DC converters. The third part covers with switching function technique applied on the standard types of DC to DC conversion. The fourth part covers with frequency changers. The fifth part covers with active filters, reactor static VAR controller, switched capacitor, inverter filter and active line current shaping circuits.
Electronic reproduction.
Keywords: Analog-to-digital converters; Frequency changers; Electric filters, Active